Electrical characteristic fluctuation of 16-nm-gate trapezoidal bulk FinFET devices with fixed top-fin width induced by random discrete dopants - Huang, Wen-Tsung (Nanoscale Res Lett, 2015)
In this work, we use an experimentally calibrated 3D quantum mechanically corrected device simulation to study the random dopant fluctuation (RDF) on DC characteristics of 16-nm-gate trapezoidal bulk fin-type field effect transistor (FinFET) devices. The fixed top-fin width, which is consistent with the realistic process by lithography, of trapezoidal bulk FinFET devices is considered in this study. For RDF on trapezoidal bulk FinFETs under the fixed top-fin width, we explore the impact of geometry and RDF on the on-/off-state current and the threshold voltage (V(th)) fluctuation with respect to different channel fin angles. For the same channel doping concentration, compared with an ideal FinFET (i.e., device with a right angle of channel fin), the off-state current is large in trapezoidal bulk FinFETs with a small fin angle. Furthermore, the short-channel effect and V(th) variation degrade as the fin angle is getting smaller. The magnitude of the normalized σV(th) increases 7% when the fin angle decreases from 90° to 70°.